2019
DOI: 10.1016/j.abd.2018.10.001
|View full text |Cite
|
Sign up to set email alerts
|

Improving skin picking diagnosis among Brazilians: validation of the Skin Picking Impact Scale and development of a photographic instrument

Abstract: BackgroundSkin picking disorder is a prevalent disorder frequently comorbid with depression and anxiety, which is underdiagnosed mainly by dermatologists. Assessment of skin picking disorder is based on instruments influenced by the awareness about skin picking disorder and comorbid symptoms. To date, there is no validated instrument for Brazilian individuals nor an instrument to evaluate the severity of skin lesions in an objective way.ObjectivesValidate the Skin Picking Impact Scale for Brazilian Portuguese … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 22 publications
0
9
0
Order By: Relevance
“…These results reflect the severity of SPD skin lesions and are a reliable way of determining skin picking habit reduction. Since previous studies have found that change in photographic instrument results is not correlated with change in depression or anxiety symptoms, 30 it can be hypothesized that the treatment applied in this study directly reduced the skin picking habit, independently of other variables.…”
Section: Discussionmentioning
confidence: 69%
See 4 more Smart Citations
“…These results reflect the severity of SPD skin lesions and are a reliable way of determining skin picking habit reduction. Since previous studies have found that change in photographic instrument results is not correlated with change in depression or anxiety symptoms, 30 it can be hypothesized that the treatment applied in this study directly reduced the skin picking habit, independently of other variables.…”
Section: Discussionmentioning
confidence: 69%
“…For Study 2, we also included a photographic instrument developed by two dermatologists to directly evaluate SPD lesions. 30 All photos were analyzed by two blinded dermatologists with the photographic instrument, which has high internal consistency and moderate reliability. This measure is important since it specifically assesses lesion severity apart from the influence of patient habit awareness or associated depressive/anxious symptoms.…”
Section: Procedures and Measuresmentioning
confidence: 99%
See 3 more Smart Citations